Implementasi Kebijakan Pelayanan Penanganan Kekerasan Terhadap Perempuan di Dinas Pemberdayaan Perempuan, Perlindungan Anak, Pengendalian Penduduk, dan Keluarga Berencana Kota Blitar - Qomaruzzaman Azam Zami; Rachel Anggita Lintang (Perspektif Administrasi Publik dan hukum, 2024)
Violence against women is a global issue that continues to increase. SIMFONI PPA data shows an increasing trend in cases of violence against women in Indonesia, with 11,712 victims in 2023. The purpose of this study is to explain how the UPTD PPA of Blitar City implements a policy of handling services for cases of violence against women and find obstacles faced in its implementation. Talcott Parsons' structural functional theory is used to analyze how social systems function in the context of protecting women to maintain stability and balance in society. This study uses qualitative, descriptive methods with data collection techniques through participatory observation, interviews, and documentation. The results are that the UPTD provides six services for protecting women and children, namely complaints, outreach, case management, shelter, mediation, and assistance. Then referring to PERPRES No. 55 of 2024, the number of services has been increased to eleven. However, social challenges such as negative stigma and limited human resources hinder policy implementation. Therefore, UPTD PPA Kota Blitar continues to strive to provide comprehensive services by involving external parties for legal and psychological assistance which then emphasizes the importance of increasing capacity and human resources to ensure effective protection services for victims of violence at the local level.